Tests on the Mechanical Properties of Polymers in the Aspect of an Attempt to Determine the Parameters of the Mooney-Rivlin Hyperelastic Model - Śliwa-Wieczorek, Klaudia; Zając, Bogusław; Kozik, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents testing of the mechanical properties of SIKA? polymer adhesives of the type PBM, PMM, PM, and PSM in the aspect of an attempt to determine the parameters of the Mooney-Rivlin hyperelastic model. The article contains a literature review on developed models for hyperelastic materials as well as a description of the autor`s own results obtained in monaxial tensile and monaxial compression tests conducted on oars and cylindrical samples, respectively. Furthermore, the results of modeling of Mooney-Rivlin hyperelastic model parameters are shown in relation to the value of average parameters for polymers after both a week and a month-and-a-half of ripening.
Keywords: hyperelastic model; hyperelasticity; polymers; adhesive joint; deformation; stresses; model hiperelastyczny; hiperelastyczność; polimery; połączenie klejowe; odkształcenia; naprężenia